1999
DOI: 10.1093/oxfordjournals.jbchem.a022381
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Ca2+/Calmodulin-Dependent Protein Kinase Phosphatase

Abstract: Calmodulin-dependent protein kinase (CaM-kinase) phosphatase dephosphorylates and concomitantly deactivates CaM-kinase II activated upon autophosphorylation, and CaM-kinases IV and I activated upon phosphorylation by CaM-kinase kinase [Ishida, I., Okuno, S., Kitani, T., Kameshita, I., and Fujisawa, H. (1998) Biochem. Biophys. Res. Commun. 253, 159-163], suggesting that CaM-kinase phosphatase plays important roles in the function of Ca2+ in the cell, because the three multifunctional CaM-kinases (CaM-kinases I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 0 publications
3
50
0
Order By: Relevance
“…Since then, two groups of investigators have independently isolated the same cDNA from different sources and have named it hFEM-2 (30) and POPX2 (31), depending on its identified function. Both groups recognized what we had found earlier during the course of our investigation, 2 the human sequence shares 80% identity with the rat Ca 2ϩ /calmodulin-dependent protein kinase phosphatase (rCaMKPase) (32); however, neither group fully investigated this possible function of the gene, other than to demonstrate that a partially purified hFEM-2 could dephosphorylate CaMKII in vitro (30). The rCaMKPase has characteristics similar to members of the PP2C family, including a dependence on divalent cations for activity and insensitivity to okadaic acid (OA), and has been shown to dephosphorylate as well as deactivate autophosphorylated CaMKII in vitro (33).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Since then, two groups of investigators have independently isolated the same cDNA from different sources and have named it hFEM-2 (30) and POPX2 (31), depending on its identified function. Both groups recognized what we had found earlier during the course of our investigation, 2 the human sequence shares 80% identity with the rat Ca 2ϩ /calmodulin-dependent protein kinase phosphatase (rCaMKPase) (32); however, neither group fully investigated this possible function of the gene, other than to demonstrate that a partially purified hFEM-2 could dephosphorylate CaMKII in vitro (30). The rCaMKPase has characteristics similar to members of the PP2C family, including a dependence on divalent cations for activity and insensitivity to okadaic acid (OA), and has been shown to dephosphorylate as well as deactivate autophosphorylated CaMKII in vitro (33).…”
supporting
confidence: 82%
“…While these studies were ongoing, the putative PPM1F-A sequence was found to share 80% identity with rCaMKPase (32), suggesting that PPM1F could act as a CaM kinase phosphatase. The rCaMKPase has been shown to dephosphorylate specifically and to deactivate CaMKI, -II, and -IV (45).…”
Section: Clone J4-3 As a Potential Cam Kinase Phosphatase-j4-3mentioning
confidence: 99%
“…In forebrain extracts, PP1 and PP2A account for the majority of phosphatase activity measured using Thr 286 -autophosphorylated CaMKII (see below) (Strack et al, 1997a). Although PP2C may make only a small contribution to CaMKII dephosphorylation in forebrain (Strack et al, 1997a), it may have more significant roles in cerebellum and other cells (Fukunaga et al, 1993;Ishida et al, 1998;Kitani et al, 1999 (Patton et al, 1990;Fukunaga et al, 1993). Although specific phosphatase complexes involved in CaMKII dephosphorylation have not been identified, a novel aspect of CaMKII regulation is that the physiologically relevant phosphatase appears to depend on the subcellular localization of the kinase.…”
Section: Pp2b Complexesmentioning
confidence: 99%
“…Ca 2+ /calmodulin-dependent protein kinase phosphatase (CaMKP) and its nuclear homolog CaMKP-N are unique protein phosphatases that specifically dephosphorylate and regulate multifunctional CaMKs such as CaMKI, II, and IV [5][6][7][8][9]. CaMKP and CaMKP-N are Mn 2+ -dependent, calyculin A/okadaic acid-insensitive Ser/Thr protein phosphatases that belong to the PPM family and share 28% homology with the catalytic domain of protein phosphatase 2C (PP2C) α [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…CaMKP and CaMKP-N are Mn 2+ -dependent, calyculin A/okadaic acid-insensitive Ser/Thr protein phosphatases that belong to the PPM family and share 28% homology with the catalytic domain of protein phosphatase 2C (PP2C) α [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%